Risk Factors for Sexual Violence in Adolescents : Literature Review - Trilia, Trilia; Nambiar, Nisha; Said, Faridah Mohd (International Journal of Health Sciences, 2023)
Introduction: Every year sexual violence cases increase and become a widely heard issue in the community. The increase in cases that occur requires research that examines what the risk fator affects. The purpose of this study was to analyze scientific articles related to what are the risk factors for sexual violence in adolescents. Material and Methods: The research employed literature review. The literature consists of journals with a travel year from 2018 to 2022. Literature collection was done through Google scholar, Pubmed, and ScienceDirect using the keyword “sexual violence”, “risk factor”, and “teenager”. Results: The results of the literature search 34.927 articles found in the database regarding entered keywords; however 34.917 articles in the last five years were excluded because they were not relevant to the author’s criteria. There were 5 articles that met the inclusion criteria, however only six articles categorized as good quality. Conclusion : Review results show that have any risk factors affecting sexual violence of a teenager, among other things gender, alcohol, age, sexual disorder, family, gadget, environmnet, disability, a poor parental education, economic, lust, religion, dating, and sexual intercourse.